2020
DOI: 10.3390/agronomy10101506
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Cropping as Affected by Phosphorus and Water Supply

Abstract: In a future exposed to threats of climate change, sustainable biomass production will be crucial. Maize (Zea mays) and sorghum (Sorghum sp.) are important crops for human and animal nutrition, as well as for bioenergy. The aim of this study was to investigate maize and sorghum in mixed cropping with soybean (Glycine max) and faba bean (Vicia faba) regarding biomass yield, drought tolerance, phosphorus (P) availability, and enzyme activity in soil as affected by the single and combined effects of water and P su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The available phosphorus also depends on the organic matter content in the soil [ 38 ]. In the presence of available phosphorus deficiency and drought conditions, it has been observed that crops grown in mixtures absorb phosphorus released in the soil from leguminous plants directly, thus allowing for plant resilience [ 39 ]. In addition, the availability of organic phosphorus is also increased by a variety of leguminous crops.…”
Section: Discussionmentioning
confidence: 99%
“…The available phosphorus also depends on the organic matter content in the soil [ 38 ]. In the presence of available phosphorus deficiency and drought conditions, it has been observed that crops grown in mixtures absorb phosphorus released in the soil from leguminous plants directly, thus allowing for plant resilience [ 39 ]. In addition, the availability of organic phosphorus is also increased by a variety of leguminous crops.…”
Section: Discussionmentioning
confidence: 99%
“…Even though intercropping has a long agronomic tradition in maintaining soil health and improving crop health and performance, the technique should further be employed for a sustainable biomass production allowing, for example, the reduction of nitrogen fertilizers when employing nitrogen-fixing legumes. Intercropping maize and sorghum (Sorghum bicolor L.) with legumes reduced the adverse effects of drought stress and phosphorous deficiency, as demonstrated in an outdoor pot trial by Eichler-Löbermann et al [9]. Under suboptimal conditions of water and phosphorous shortage a higher yield stability of the crop mixtures was demonstrated, which makes them a suitable agronomic alternative to sole cropped maize or sorghum.…”
mentioning
confidence: 94%